Delivery of neutrophil membrane encapsulated non-steroidal anti-inflammatory drugs by degradable biopolymer microneedle patch for rheumatoid arthritis therapy. (April 2023) - Lin, Yixuan; Chen, Yang; Deng, Ronghui; Qin, Hao; Li, Nan; Qin, Yuting; Chen, Hanqing; Wei, Yaohua; Wang, Zeming; Sun, Qing; Qiu, Wenyi; Shi, Jian; et al.
Abstract: Rheumatoid arthritis (RA) is a common chronic autoimmune disease and eventually ends in severe disability and death. RA has no cure, but there are some treatments for decreasing the severity of various symptoms. For example, pain management of RA by non-steroidal anti-inflammatory drugs (NSAIDs), neutralization of the inflammatory cytokines (or block their functions) of RA by specific biologics. However, the clinical benefit is limited due to their low permeability and poor bioavailability. Meanwhile, the system toxicity for long-term use of NSAIDs is another focal issue. Herein, degradable biopolymer microneedle patch was designed and synthesized. In this dual drug delivery patch, NSAIDs were encapsulated by polymeric nanoparticles, which were coated by the neutrophil membrane, followed by loaded into the microneedle patch for local transdermal delivery. When applied to the murine models, the microneedle patch gradually dissolves and releases the contained nanoparticles. Coating of neutrophil membrane provides the nanosized NSAIDs with the capability of cytokine binding and inflammatory joint tropism. Based on inflammatory microenvironment regulation by cytokine absorption and cyclooxygenase-2 inhibition, the microneedle shows a significant local anti-inflammatory therapeutic effect on mouse model of collagen-induced arthritis and rat model of adjuvant-induced arthritis. Further development based on this advanced strategy may provide additional therapeutic options for RA treatment. Graphical Abstract: Lin et al. design a therapeutic nanoparticles-loaded soluble microneedle patch for anti-inflammatory treatment of rheumatoid arthritis. The microneedle patch allows nonsteroidal anti-inflammatory drugs to be applied to the animals with less systemic toxicity, and simultaneous delivery of neutrophil membrane enhances the inflammatory tropism and anti-inflammatory effects. It may provide additional therapeutic options for rheumatoid arthritis treatment. ga1 Highlights: A therapeutic nanoparticles-loaded microneedle patch was designed for anti-inflammatory treatment of rheumatoid arthritis. The microneedle patch allows nonsteroidal anti-inflammatory drugs to be applied to the animals with less systemic toxicity. Simultaneous delivery of neutrophil membrane enhances the inflammatory tropism and anti-inflammatory effects. It may provide additional therapeutic options for rheumatoid arthritis treatment.